2010
DOI: 10.1590/s1807-03022010000100006
|View full text |Cite
|
Sign up to set email alerts
|

Partial sums of analytic functions of bounded turning with applications

Abstract: Abstract.In this article, we determine certain conditions under which the partial sums of the multiplier integral operators of analytic univalent functions of bounded turning are also of bounded turning.Mathematical subject classification: 30C45.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…There are different techniques of studying the class of bounded turning functions, such as using partial sums or applying Jack Lemma [5]- [7].…”
Section: Example 1 (See Figs 1 and 2)mentioning
confidence: 99%
“…There are different techniques of studying the class of bounded turning functions, such as using partial sums or applying Jack Lemma [5]- [7].…”
Section: Example 1 (See Figs 1 and 2)mentioning
confidence: 99%
“…Recently, Darus and Ibrahim [4] and Hayami et al [5] have shown some interesting results for some partial sums of analytic functions. Now, we derive the following.…”
Section: Partial Sumsmentioning
confidence: 99%
“…In addition, Darus and Ibrahim [11] specified the assumptions, which indicated that the partial sums of functions of bounded turning are also of bounded turning. Recently, Darus and Ibrahim [12] …”
Section: Introductionmentioning
confidence: 99%